Classification and Evaluation of Volcanic Rock Reservoirs Based on the Constraints of Energy Storage Coefficient - Sun, Wen-Tie; Lou, Yi-Shan; Kamgue Lenwoue, Arnaud Regis; Li, Zhong-Hui; Zhu, Liang; Wu, Hui-Mei (Frontiers in Earth Science, 2022)
The current classification and evaluation methods of volcanic rock reservoirs have low accuracy and cannot effectively provide guidance for the selection of volcanic rock gas reservoirs which have efficient properties for gas production. In this research, we have analyzed the lithology, lithofacies, reservoir space type, pore combination mode and reservoir microscopic characteristics of volcanic reservoirs using the energy storage coefficient as a constraint. Then, the method of reservoir classification was proposed. The results showed that: (1) The energy storage coefficient can better characterize the single-layer productivity of gas wells. The volcanic rock reservoirs in Wangfu Gas Field can be subdivided into three categories by considering the energy storage coefficient; (2) Type I reservoirs mainly develop structural fracture-matrix dissolution pores, structural fractures-intercrystalline micropores and matrix dissolution pores. Type II reservoirs mainly develop matrix dissolution pores and residual intergranular pores, and Type III reservoirs are dominated by structural fractures. From Type I to Type III reservoirs, the skewness of the mercury intrusion curve and the sorting coefficient deteriorated, the physical properties of the reservoir and the maximum mercury saturation and other parameters also decreased, whereas the displacement pressure and the median saturation pressure increased; (3) The characteristics of conventional and special logging curves of typical reservoirs were comprehensively analyzed , the combination of sensitivity parameters reflecting gas-bearing properties and logging curves was optimized. Furthermore, a reservoir classification chart was established, and the results enabled to confirm the choice of the reservoir and demonstrated that the standard classification has high accuracy; (4) The diagenesis processes such as weathering, leaching and dissolution improved the physical properties of the reservoir. The research results can effectively provide guidance for the evaluation of the "sweet spot" of volcanic rock reservoirs.